Rhoh deficiency reduces peripheral T-cell function and attenuates allogenic transplant rejection - Porubský, Štefan; Wang, Shijun; Kiss, Eva; Dehmel, Stefan; Bonrouhi, Mahnaz; Dorn, Tatjana; Luckow, Bruno; Brakebusch, Cord; Gröne, Hermann-Josef (European journal of immunology, 2011)
Rhoh is a hematopoietic system-specific GTPase. Rhoh-deficient T cells have been shown to have a defect in TCR signaling manifested during their thymic development. Our aims were to investigate the phenotype of peripheral Rhoh-deficient T cells and to explore in vivo the potential benefit of Rhoh deficiency in a clinically relevant situation, in which T-cell inhibition is desirable. In murine allogenic kidney transplantation, Rhoh deficiency caused a significant 75% reduction of acute and chronic transplant rejection accompanied by 75% lower alloantigen-specific antibody levels and significantly better graft function. This effect was independent of the lower T-cell numbers in Rhoh-deficient recipients, because injection of equal numbers of Rhoh-deficient or control T cells into kidney transplanted mice with SCID led again to a significant 60% reduction of rejection. Mixed lymphocyte reaction revealed that the weaker alloreactivity was associated with a 85% lower cytotoxicity and a 50-80% lower cytokine release in Rhoh-deficient T cells without an influence on the secretion itself. Antigen uptake and presentation in DC were unaffected by Rhoh deficiency. These findings stress the importance of Rhoh for the function of peripheral T cells.
First published: 13 October 2010
Gesehen am 12.01.2023